Remote Cerebellar Hemorrhage after Removal of Large Convexity Meningioma - Shrestha, Dinuj; Shrestha, Janam; Rajbhandari, Pravesh; Shrestha, Resha; Pant, Basant (Nepal Journal of Neuroscience, 2020)
Remote cerebellar hemorrhage is a rare postoperative complication. It can occur after infratentorial or supratentorial craniotomies, later being more common. Remote cerebellar hemorrhage is considered to be a self-limited and benign condition. The exact pathophysiology of remote cerebellar hemorrhage remains unclear, but reports have suggested an association with excessive loss of cerebrospinal fluid.We report a case of remote cerebellar hemorrhage after supratentorial craniotomy for large convexity meningioma without excessive loss of cerebrospinal fluid.